Sex predetermination technology: a critical analysis from Islamic perspective - Haneef, Sayed Sikandar Shah (Zes Rokman Resources, 2016)
Tremendous advancement in medical science, among others, has resulted in the mushrooming of fertility facilities thereby enabling both infertile and normal couples to predetermine the sex of their future babies the world over. The situation is more acute in some Muslim countries where the preference for male gender is predominately a sociological reality. Muslim couples with resources, therefore, have no qualm in the sexing of their progeny particularly when their psychological fear is dispelled by some permissive juristic views about gendering.. The ground reality of such choices in some Middle Eastern countries bear testimony to this fact. As to whether such use of medical technology is consistent with Islamic larger ethical vision of reproduction in Islam is a contested issue especially among the Muslims legists. This paper, therefore, proposes to critically unveil the fallacy of general advocacy of technological sexing from Islamic ethico-legal perspectives.